Time from diagnosis to 2nd treatment is a promising surrogate for overall survival in patients with advanced stage follicular lymphoma. Issue 12 (14th October 2020) - Soumerai, Jacob D.; Ni, Andy; Alperovich, Anna; Batlevi, Connie; Bantilan, Kurt S.; Fischer, Thais; Copeland, Amanda R.; Smith, Katy; Ying, Zhitao; Younes, Anas; Zelenetz, Andrew D.
Abstract: It is difficult to demonstrate an overall survival (OS) benefit in trials of immediate therapy vs observation in follicular lymphoma (FL). Time to 2nd treatment (TT2T) may be a preferred endpoint. We identified 584 consecutive patients at our institution with advanced stage FL grade 1–3 A for whom intention was observation ( n  = 248) or therapy ( n  = 338). Median time to 1st treatment (TT1T), TT2T, and OS were estimated (subdistribution function). Modified Kendall's tau (mKτ) was used to assess correlation between survival endpoints. Among initially observed patients, median TT1T was 3.3 years, TT2T was 12.1 years, 10-year treatment-free survival was 23%, and 10-year OS was 82%. TT2T was strongly correlated with OS following initial observation (mKτ 0.46, p  = .004) or therapy (mKτ 0.53, p  < .0001), while duration of observation was not. TT2T is a potential surrogate for OS. Given the outstanding survival in this population, early intervention trials should focus on identifying high risk patients.